Identification and characterization of bisbenzimide compounds that inhibit human cytomegalovirus replication. (9th December 2021) - Falci Finardi, Nicole; Kim, HyeongJun; Hernandez, Lee Z.; Russell, Matthew R. G.; Ho, Catherine M-K; Sreenu, Vattipally B.; Wenham, Hannah A.; Merritt, Andy; Strang, Blair L.
Abstract : The shortcomings of current anti-human cytomegalovirus (HCMV) drugs has stimulated a search for anti-HCMV compounds with novel targets. We screened collections of bioactive compounds and identified a range of compounds with the potential to inhibit HCMV replication. Of these compounds, we selected bisbenzimide compound RO-90-7501 for further study. We generated analogues of RO-90-7501 and found that one compound, MRT00210423, had increased anti-HCMV activity compared to RO-90-7501. Using a combination of compound analogues, microscopy and biochemical assays we found RO-90-7501 and MRT00210423 interacted with DNA. In single molecule microscopy experiments we found RO-90-7501, but not MRT00210423, was able to compact DNA, suggesting that compaction of DNA was non-obligatory for anti-HCMV effects. Using bioinformatics analysis, we found that there were many putative bisbenzimide binding sites in the HCMV DNA genome. However, using western blotting, quantitative PCR and electron microscopy, we found that at a concentration able to inhibit HCMV replication our compounds had little or no effect on production of certain HCMV proteins or DNA synthesis, but did have a notable inhibitory effect on HCMV capsid production. We reasoned that these effects may have involved binding of our compounds to the HCMV genome and/or host cell chromatin. Therefore, our data expand our understanding of compounds with anti-HCMV activity and suggest targeting of DNA with bisbenzimide compounds may be a useful anti-HCMV strategy.